Resilience to Online Privacy Violation: Developing a Typology of Consumers - Jelena Budak; Edo Rajh; Bruno Škrinjarić (Scientific Annals of Economics and Business, 2023)
This study examines which segments of population with similar resilience to online privacy violation, severity of online privacy violation, and attitudes towards online privacy concern exist in Croatia, and whether they can be differentiated by demographic characteristics and attitudes towards other online constructs. Research is performed on a representative sample of Croatian Internet users who experienced online privacy violation. The survey data were analyzed using factor analysis, k-means cluster analysis, chi-square test and ANOVA. The findings indicate three groups of consumers with: (1) low-resilience, (2) moderate-resilience, and (3) high-resilience; who differ in age, income, and online buying habits.